Prevalence and characteristics of Staphylococcus aureus isolated from Kazak cheese in Xinjiang, China. (May 2021) - Cai, Huixue; Kou, Xiaomeng; Ji, Hua; Wang, Xin; Wang, Haixia; Zhang, Yan; Lu, Shili; Li, Baokun; Dong, Juan; Wang, Qingling; Zhou, Jing; Hu, Die
Abstract: Staphylococcus aureus ( S. aureus ) is a common pathogen found in dairy products whose enterotoxins are the main pathogenic factors that cause food poisoning. In this study, a total of 399 samples of retail Kazak cheese collected from 4 regions in Xinjiang (China) were qualitatively and quantitatively analyzed for the presence of bacteria. Among them, 56 (14%, 95% CI: 10.6–17.4%) samples were found to be positive for S. aureus, and their distribution and degree of contamination vary from region to region, with 19.4% (31/160) in Altay, 10.7% (23/215) in Yining and 22.2% (2/9) in Tacheng, and corresponding geometric mean level of 5.8, 4 and 3 most probable number/gram, respectively. In addition, 62 strains of S. aureus were isolated from the positive samples. The most frequently detected gene in the 3 regions was staphylococcal enterotoxin gene c ( sec ) (29%), followed by sea (25.6%), see (9.8%), sed (8%), seb (3.2%). Finally, the analysis of 13 resistance genes and the minimum inhibitory concentration (MIC) of 12 antibiotics in 62 strains of S. aureus identified 13 methicillin-resistant S. aureus strains (21%). The S. aureus isolates showed most resistance to penicillin (69.3%), followed by erythromycin (27.4%) and clindamycin (24.2%). There were 17 (27.4%) strains of S. aureus with multiple drug resistance, and one strain was even resistant to 10 antibiotics. A high frequency of bla Z (45.2%) and mec A (16.1%) resistance genes was found among the S. aureus isolates. Among the penicillin-resistant strains, 60.5% (26/43) had the bl aZ gene. The findings of this study suggest that S. aureus has spread across different regions of Xinjiang. The presence of S. aureus strains in Kazak cheese during the selling period poses a potential threat to public health and underscores the need for the continuous monitoring of these cheeses. Highlights: The comprehensive study on Staphylococcus aureus isolated from retail artisanal Kazak cheese in Xinjiang, China. High prevalence of S. aureus in Kazak cheese. S. aureus strains exhibited multiple drugs and carried various enterotoxin and antimicrobial resistance genes. S. aureus strains are opportunistic pathogens, which are potential safety hazards for consumers. S. aureus may spread among different regions in Xinjiang.